Assessing Customer Satisfaction at the NIST Research Library: Essential Tool for Future Planning. - Rosa Liu; Nancy Allmang (Issues in Science and Technology Librarianship)
This article describes a campus-wide customer satisfaction survey undertaken by the National Institute of Standards and Technology (NIST) Research Library in 2007. The methodology, survey instrument, data analysis, results, and actions taken in response to the survey are described. The outcome and recommendations will guide the library both strategically and operationally in designing a program that reflects what customers want -- in content, delivery, and services. The article also discusses lessons learned that other libraries may find helpful when planning a similar survey. [ABSTRACT FROM AUTHOR]